In memoriam - Winn, Alice (Alice Mary Felicity), 1992- (Alfred A. Knopf, 2023)
"It's 1914, and World War I is ceaselessly churning through thousands of young men on both sides of the fight. The violence of the front feels far away to Henry Gaunt, Sidney Ellwood and the rest of their classmates, all of whom are safely ensconced in their idyllic boarding school in the English countryside. They receive weekly dispatches from The Preshutian, their school newspaper, informing them of older classmates killed or wounded in action. Their heroic deaths only make the war more exciting. Gaunt, half-German, is busy fighting his own private battle- an all-consuming infatuation with his best friend, the gorgeous, rich, charming Ellwood-not having a clue that Ellwood is pining for him in return. Meanwhile, Gaunt's German mother and twin sister ask him to enlist as an officer in the British army to protect the family from the anti-German attacks they're already facing. Gaunt signs up immediately, relieved to escape his overwhelming feelings for Ellwood. The front is horrific, of course, and though Gaunt tries to dissuade Ellwood from joining him on the battlefield, Ellwood soon rushes to join him, fueled by his education in Greek heroics and romantic wartime poetry. Before long, most of their classmates have followed suit. Once in the trenches, the boys become intimately acquainted with the harsh realities of war. Ellwood and Gaunt find fleeting moments of solace in one other, but their friends are all dying, often in front of them, and no one knows when they'll be next"--